2023
DOI: 10.1111/evj.13935
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of equine sarcoids: A systematic review

Abstract: BackgroundThe sarcoid is the most common equine cutaneous neoplasm. Evidence‐based treatment of this condition is often lacking, and selection of treatment modality based on clinical experience or anecdotal evidence.ObjectivesTo assess the quality of the currently available best evidence regarding the treatment of the equine sarcoid.Study designSystematic review.MethodsIn compliance with PRISMA guidelines, literature searches were performed in PUBMED, Web of Science, CAB Abstracts, EMBASE (Ovid) and Scopus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(140 reference statements)
0
2
0
2
Order By: Relevance
“…The lack of routinely accepted standardised outcome measure for the treatment of sarcoids makes comparison between studies very difficult. (Offer et al, 2024) Though these recurrence rates are marginally higher than those reported in the literature (sarcoid regression rates of 83-89% with sole laser excision), Compston et al, 2016) this is highly likely to be influenced by numerous factors, including greater length of follow up period in this study, and differences in case selection and treatment populations. These horses were all referred to the hospital for further evaluation and treatment, and by definition were positioned at the more severe end of sarcoid phenotype presentation.…”
Section: Treatment Protocolsmentioning
confidence: 59%
“…The lack of routinely accepted standardised outcome measure for the treatment of sarcoids makes comparison between studies very difficult. (Offer et al, 2024) Though these recurrence rates are marginally higher than those reported in the literature (sarcoid regression rates of 83-89% with sole laser excision), Compston et al, 2016) this is highly likely to be influenced by numerous factors, including greater length of follow up period in this study, and differences in case selection and treatment populations. These horses were all referred to the hospital for further evaluation and treatment, and by definition were positioned at the more severe end of sarcoid phenotype presentation.…”
Section: Treatment Protocolsmentioning
confidence: 59%
“…Although numerous treatments against ES disease are currently in widespread use, double-blinded placebo-controlled studies critically assessing the efficacy and sustainability are lacking for most of these treatment options. 45 The study design of the present investigation was not only placebo-controlled and randomized but also doubleblinded. Therefore, it fulfills every criterion for a rigorously controlled and unbiased investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Offer et al . (2023) 14 revisa los méritos relativos y las tasas de regresión asociados a varios tratamientos contra sarcoides, pero concluye que hay insuficientes recomendaciones para evaluar uno sobre el otro en todas las situaciones, mientras Johnson et al . (2023) 15 explora las evolución de las aplicaciones de la terapia extracorporal por ondas de choque.…”
Section: Discussionunclassified
“…Nevertheless, the included reviews in this collection offer some pertinent information for the general practitioner. Offer et al 14 review the relative merits and regression rates associated with various sarcoid treatments, but conclude there are insufficient recommendations to rate one over the other in all situations, whilst Johnson et al 15 explore the evolving clinical applications of extracorporeal shockwave therapy. A practical take home message on maximising the diagnostic power of blood cultures was that although blood for this purpose is often taken during intravenous catheter placement for convenience, this may increase the potential for contamination and a non‐diagnostic result 16 …”
Section: Informative Summaries For the First Opinion Practitionermentioning
confidence: 99%